Disability Type and Risk of Sexual and Stalking Victimization in a National Sample: A Lifestyle–Routine Activity Approach - Reyns, Bradford W. (Criminal justice and behavior, 2019)
Research findings from national samples indicate that people with disabilities have a higher risk of sexual and stalking victimization than their counterparts without disabilities. While this body of research indicates that disability is a risk factor for interpersonal victimization independent of known risk factors derived from the lifestyle-routine activity perspective, it has not yet been established whether the risk factors of victimization vary across disability type. Using survey data from approximately 40,000 college students from across the United States, this study addresses this issue by examining lifestyle-routine activity risk factors for victimization among subsamples of individuals with no disability, physical disabilities, mental disabilities, and learning disabilities. Results from multivariate binary logistic regression analyses indicate that risk factors for victimization vary across groups, with the greatest number of significant risk factors observed for students with no disabilities.